Prevalence of Elevated Serum Creatinine Concentration in Dogs Presenting to a Veterinary Academic Medical Center (2010–2014) - Babyak, J.M. (J Vet Intern Med, 2017)
BACKGROUND: The epidemiology of kidney disease is not extensively described in dogs. HYPOTHESIS/OBJECTIVES: To better understand the prevalence of elevated serum creatinine concentration in dogs. ANIMALS: Client‐owned dogs. METHODS: A retrospective, observational cross‐sectional study design was used. We made a dataset of 115,631 hospital visits of all dogs presenting from October 2010 to October 2014. We estimated the prevalence and risk of elevated serum creatinine, defined as >1.6 mg/dL, in evaluated dogs. RESULTS: Of 115,631 visits, 98,693 were outpatient visits and 16,938 were hospital admissions. Among outpatient visits, 9,983 (10.1%) had serum creatinine assessment (4,423 [44.3%] visits were first visits), whereas, among hospital admissions, 12,228 (60.0%) had at least 1 serum creatinine (7,731 [75.6%] admissions were first admissions). The prevalence of elevated serum creatinine concentration in all evaluated dogs was 11.5% (95% CI: 11.0%, 11.9%); 10.2% (95% CI: 9.6%, 10.8%) of inpatients and 12.9% (95% CI: 12.1%, 13.8%) of outpatients had elevated serum creatinine concentration. The relative risk (RR) of elevated serum creatinine concentration was significantly higher in geriatric dogs (outpatient RR 1.45 [95% CI: 1.23, 1.70], inpatient RR 1.43 [95% CI: 1.16, 1.76]) and lower in young dogs (outpatient RR 0.39 [95% CI: 0.26, 0.59], inpatient RR 0.44 [95% CI: 0.32, 0.62]) when compared to the measured population risk. CONCLUSIONS AND CLINICAL IMPORTANCE: When selected for laboratory evaluation, the proportion of dogs presenting to an academic medical center with evidence of kidney injury is high compared to previous reports and might reflect a population of sicker dogs.